Pengaruh Suplementasi L-Arginin Dalam Pakan Terhadap Organ Pencernaan Ayam Broiler - Viktor Fernandes Fahik; Charles V. Lisnahan; Gerson F. Bira (JAS, 2021)
This research was conducted in the enclosure of the Faculty of Agriculture, University of Timor, Sasi sub-district, Kefamenanu city, North Central Timor district for 42 days from April to May 2021. The aim of the study was to determine the effect of L-arginine supplementation in feed on the digestive organs of broiler chickens. This study used 96 Day Old Chick broilers. The research method used was a completely randomized design (CRD) consisting of 4 treatments and 4 replications. Each experimental unit consisted of 6 broilers. The treatments given consisted of T0: control feed, T1: control + 0.5% L-arginine, T2: control + 0.75% L-arginine, T3: control + 1.00% L-arginine. The variables observed were liver weight, bile weight, pancreatic weight, gizzard weight, intestinal length and small intestine weight. The data obtained were analyzed using statistical package software for the social sciences (SPSS 20). The analysis showed that the addition of L-arginine had no significant effect (P<0.05) on liver weight, bile weight, pancreatic weight, gizzard weight, intestinal length and small intestine weight. Based on these results and discussion, it can be concluded that the supplementation of the amino acid L-arginine 0.75% in broiler chicken feed can affect the weight of the digestive organs of the gizzard, while the weightof the liver, bile, panceas, intestinal weight have on significant effect.